2021
DOI: 10.1016/j.jchromb.2021.122846
|View full text |Cite
|
Sign up to set email alerts
|

Improved LC-MS/MS method for the determination of 42 neurologically and metabolically important molecules in urine

Abstract: Simultaneous determination of kynurenines, neurotransmitters, pterins and steroids linked to various neurological and metabolic diseases have important diagnostic significance for related pathology and drug monitoring. An improved, sensitive and selective ultra-high performance liquid chromatography coupled to electrospray ionization triple quadrupole mass spectrometric (UHPLC-MS/MS) method, based on our earlier publication, has been proposed for the quantitative measurement of 42 metabolites in human urine. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In order to investigate the effects of the type of buffer, we selected three ammonium-based buffers. Ammonium formate was selected because it is the main constituent of the proposed mobile phase and the most widely used volatile buffer for HPLC-MS separations [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. We also selected ammonium acetate because it is frequently used for the analysis of pterins in biological samples [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate the effects of the type of buffer, we selected three ammonium-based buffers. Ammonium formate was selected because it is the main constituent of the proposed mobile phase and the most widely used volatile buffer for HPLC-MS separations [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. We also selected ammonium acetate because it is frequently used for the analysis of pterins in biological samples [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Though strongly suggesting that the first step of H4Bip oxidation led to the release of qH2Bip, these studies, conducted mainly by liquid chromatography coupled to UV–Vis detection, showed that it was very difficult to separate these molecular species [ 24 , 25 ]. Consequently, in the era of the gene therapy of dopamine and serotonin disorders [ 26 ], no current method to determine pterins [ 17 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] allows to quantify qH2Bip. The available data on qH2Bip remain scarce and conflicting [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature 27 reported that renal function and body weight are two important covariates for clearance, therefore, they should be fully considered as components when determining the individual dose of clofarabine. 27 For a basis for optimizing the schedule of clofarabine administration, urine concentration should be standardized by the basal creatinine level. At present, the quantitative method ultimately remains qualitative in that clofarabine can relate only to positive or negative aspects of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the dilution method is frequently adopted for urine sample preparation because it is not dependent on sample preparation and the effects of the matrix have no impact on the validated LOQs or the ability to detect in urine samples. [25][26][27] In this study, the dilution method was adopted to simplify the preparation of the urine sample and the absolute recovery rates of clofarabine were greater than 85.00% at 5.00, 30.00 and 800.00 ng mL −1 .…”
Section: Sample Preparationmentioning
confidence: 99%
“…The levels of serum uremic toxins were measured according to previously published methodologies using ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) [ 34 , 41 , 42 ]. MRM transition of indoxyl sulfate was 211.9/131.9 using − 50 V as declustering potential and − 25 V as collision energy, retention time: 11.48 min.…”
Section: Methodsmentioning
confidence: 99%